Consumer Decisions in the Bandung Fruit Market: A Study on Quality and Price - Aldy Rizki Mulyana; Bambang Sucipto; Atep Suhendar (Innovation Business Management and Accounting Journal, 2024)
The purpose of this study was to determine how much influence product quality and price have on purchasing decisions at Rizki Illahi Store, Caringin Market, Bandung. The population of this study were customers of Rizki Illahi Store Caringin Market Bandung. The sample used in this study amounted to 60 respondents. The data analysis method used is descriptive quantitative and multiple linear regression analysis with SPSS tools. Descriptive survey method is a research method that takes samples from a population and uses a questionnaire as a data collection tool. In this study data and information were collected from respondents using a questionnaire or questionnaire. The results of this study indicate that there is an effect of product quality on purchasing decisions, there is an effect of price on purchasing decisions, and there is an effect of product quality and price on purchasing decisions at Rizki Illahi Store Caringin Market Bandung. by 69.5%. This means that product quality and price can explain the variation in purchasing decisions at Rizki Illahi Store Caringin Market Bandung by 69.5%.